Antecedents of organizational citizenship behavior among the academic staff in Begemidir college of teacher education - Taye, Berhan Kefyalew; Gebremeskel, Melaku Mengistu (Bahir Dar Journal of Education, 2023)
The purpose of this study was to examine the organizational citizenship behavior of the staff and its precursors at Begemidir College of teacher education. A correlational survey design that involved 96 instructors recruited through a comprehensive sampling technique was employed. Questionnaire was used to collect data that were analyzed using descriptive and inferential statistics. The result indicated that instructors demonstrated above-average mean scores in all the dimensions of organizational citizenship behavior. It also revealed that organizational support and job satisfaction had a moderate relationship with altruism, civic virtue and sportsmanship while they had a modest relationship with courtesy and conscientiousness. On the other hand, there was a strong relationship between organizational commitment and altruism, civic virtue, courtesy, and sportsmanship. Overall, while OCB had a strong relationship with organizational commitment, it had a moderate relationship with organizational support and job satisfaction. Whereas organizational commitment has a positive and significant contribution to all organizational citizenship dimensions; job satisfaction did not influence all of them. Organizational support has a significant contribution to altruism, civic virtue, sportsmanship, and organizational citizenship behavior. Hence, it was suggested that the college should constantly work on the functions of organizational commitment and support to promote organizational citizenship behavior and ensure sustainable organizational development.